Stochastic methods for boundary value problems : numerics for high-dimensional PDEs and applications - Sabelfeld, Karl K; Simonov, Nikolai A (De Gruyter, 2016)
This monograph is devoted to random walk based stochastic algorithms for solving high-dimensional boundary value problems of mathematical physics and chemistry.It includes Monte Carlo methods where the random walks live not only on the boundary, but also inside the domain.